Trajetórias de sujeitos em situação de refúgio em relação às organizações humanitárias: possibilidades de acolhimento de sírios em São Paulo e Toronto - Pucci, Fabio Martinez Serrano (2021)
The objective of this dissertation is to relate Syrian refugees’ trajectories to the settlement infrastructure of humanitarian organizations – governmental, from the civil society and the Arab diaspora. I contend that the fragmentation and ambiguity of specific policies towards refugees in Brazil lead them to seek settlement in religious organizations linked to the Arabs. I also examine the extent to which Syrian newcomers established lasting social connections with the Arabs in Brazil. Finally, I carried out a comparative study case on Syrian refugees in Toronto, Canada, where there is a Private Sponsorship Program in which Canadian citizens and permanent residents voluntarily commit themselves to resettling refugees for one year. I adopted the following theoretical framework: Bourdieu (social capital), Glick-Schiller et al. (modes of incorporation at the individual level), Portes and Rumbaut (modes of incorporation at the organizational level), Brubaker and Cooper (identification), Simmel (religion and religiosity), Agier, Fassin and Barnett (humanitarianism). I adopted qualitative methods, which consist of interviews with Syrians in a refugee situation, Arabs and professionals who work in humanitarian organizations. The data analysis and codification are based on the constructive approach of Grounded Theory. The main finding is that Syrians in a refugee situation and the Arabs established fragile bonds. This is due to the weak levels of identification in both national origin and religious affiliation between the two groups. However, there are strong levels of both class and professional identification. Religious transnational networks facilitated the access of some subjects in a refugee situation to the settlement infrastructure of churches and mosques. Religiosity and social connections with sheikhs and priests were determinant in those trajectories. However, the better possibilities of settlement were found in the organizations not linked to the Arabs. Finally, some Syrians avoided obtaining help from humanitarian organizations, rejecting the “refugees” label and asserting their ability to make their own decisions.